The Effect Of Farmers’ Characteristics, Ihsan Attitudes, Economic Conditions, And Socio-Cultural Environment Support On Farmer Behaviors - Hendrarini, Hamidah; Soedarto, Teguh (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to analyze the effect of farmers’ characteristics, ihsan attitudes, economic conditions, and socio-cultural environment support on farmer behaviors to meet food needs in realizing household food security, with the government role as a moderator of the relationship between farmer behaviors and their household food security. All household heads who were the respondents in this research worked as farmers. (1) the better the farmer characteristics were, the better the farmer behaviors to meet food needs would be, (2) ihsan attitudes affected Farmer behaviors to meet their needs, (3) Farmers’ Economic Conditions affected Farmer behaviors to meet food needs, (4) the results of the analysis using WarpPLS showed that Socio-Cultural Environment Support insignificantly affected Farmer behaviors to meet food needs, (5) Farmer behaviors to meet needs had an effect on their household Food Security, (6) the Government Role along with Farmer behaviors to meet food needs can further encourage farmers to realize farmer household food security. Ihsan attitudes of farmers as household heads supported by the attitudes of all family members are manifested in the spirit of working hard, working together and working sincerely. Ihsan attitudes become an interesting part to be studied more deeply by the researchers and it is a novelty or authenticity in this research.